Game-Based Learning: Possibilities of an Instrumental Approach to the FEZ Game for the Teaching of the Orthographic Drawings System Concepts - Daniel Nipo; David Gadelha; Mirian da Silva; Andiara Lopes (Journal on Interactive Systems, 2023)
Challenges and rewards are integral to the logic of digital games, and through them, users can learn and develop various skills. When games are employed in educational contexts, they can enhance creativity and contribute to students' development. The Game-Based Learning (GBL) methodology is grounded in the use of games in the educational context, whether they are meant for educational or entertainment purposes. This article aims to investigate whether the digital puzzle game called FEZ - which takes place in a three-dimensional scenario where the player interacts through two-dimensional views - can be used for teaching geometry, specifically from the perspective of Descriptive Geometry for learning concepts about the System of Views. To achieve this goal, we analyzed FEZ from the perspective of the Instrumental Approach as an educational resource for teaching concepts of the Orthographic Drawings System. As a result, we identify similar characteristics between the Orthographic Drawings System and the design aspects of the FEZ game that suggest the possibility of using this game as a didactic resource.